Can oral caffeine decrease postoperative opioid consumption following posterior spinal fusion in adolescent idiopathic scoliosis? A randomized placebo-controlled trial - Anne Stuedemann, MSN, RN, CPNP; Richard M Schwend, MD FAAP FAOA; Kenneth A. Shaw, MD; Nicolette Saddler, MSN, APRN, FNP-C; Michon Huston, PA-C; Michael Benvenuti, MD; Julia Leamon, MSN, RN, CPN; Ashley K. Sherman, MA; John Anderson, MD (North American Spine Society Journal)
ABSTRACT: Background: Current studies have examined the efficacy of opioid-sparing analgesics primarily in adult surgical populations, while fewer guide pediatric postoperative pain treatment. Caffeine exerts most of its biological effects by binding to adenosine receptors, which are important for modifying pain and inflammation. Caffeine's ability to modulate pain following posterior spinal fusion (PSF) for adolescent idiopathic scoliosis (AIS) has not been previously assessed. Methods: The hospital investigational drug study (IDS) pharmacy provided either a treatment dose or placebo dose of caffeine to be given to the patient and was also in charge of randomization for the study. Results: There were 24 patients in the caffeine group (mean 14.3±1.5 years, 91.7% female) and 27 in the control group (mean 14.8±1.4 years, 88.9% female). Postoperative opioid usage was lower in the caffeine cohort for POD 1 (18.6 MME vs. 21.6 MME; p=.19), but this difference was not statistically significant. Opioid usage decreased in the caffeine study group for POD 1 (caffeine: 0.35 MME/kg vs. 0.4 MME/kg; p=.19) and mean daily total opioid usage over the hospital stay (caffeine: 0.32 MME/kg vs. 0.37 MME/kg; p=1), but these differences were not statistically significant. The caffeine study group demonstrated a mean reduction in total opioid consumption over the hospital stay of 5 MME. Conclusions: Oral caffeine use resulted in an average reduction of 5 MME opioid consumption, equivalent to 5 mg of hydrocodone. While this trial was underpowered to definitively assess the outcome, oral caffeine shows potential as an adjunct medication for opioid stewardship in AIS patients. This trial's reported mean total oral opioid consumption range of 0.83 to 0.92 MME/kg is lower than the amounts typically observed in clinical trials. This finding could indicate a successful strategy in reducing opioid use, which aligns with current medical efforts for opioid stewardship.